કૂજન, ધોરણ-૨,સેમેસ્ટર-૧ - (:unkn) unknown (Gujarat State Board of School Textbooks (GSEB), 2015)
The book is a Gujarati medium school textbook for class-2, semester-1.
Koojan, Class-2, Semester-1
Keywords: Gujarati; કૂજન; ધોરણ-૨; સેમેસ્ટર-૧; Koojan; Class-2; Semester-1; Gujarati; Gujarati; Gujarati